Development and Characterization of Novel Polymorphic Microsatellite Markers for Tapinoma indicum (Hymenoptera: Formicidae). Issue 4 (23rd July 2021) - Lim, Li Yang; Ab Majid, Abdul Hafiz
Abstract: Tapinoma indicum (Forel) (Hymenoptera: Formicidae) is a nuisance pest in Asia countries. However, studies on T. indicum are limited, especially in the field of molecular biology, to investigate the species characteristic at the molecular level. This paper aims to provide valuable genetic markers as tools with which to study the T. indicum population. In this study, a total of 143, 998 microsatellite markers were developed based on the 2.61 × 10 6 microsatellites isolated from T. indicum genomic DNA sequences. Fifty selected microsatellite markers were amplified with varying numbers of alleles ranging from 0 to 19. Seven out of fifty microsatellite markers were characterized for polymorphism with the Hardy–Weinberg equilibrium (HWE) and linkage disequilibrium (LD) analysis. All seven microsatellite markers demonstrated a high polymorphic information content (PIC) value ranging from 0.87 to 0.93, with a mean value of 0.90. There is no evidence of scoring errors caused by stutter peaks, no large allele dropout, and no linkage disequilibrium among the seven loci; although loci Ti-Tr04, Ti-Tr09, Ti-Te04, Ti-Te13, and Ti-Pe5 showed signs of null alleles and deviation from the HWE due to excessive homozygosity. In conclusion, a significant amount of microsatellite markers was developed from the data set of next-generation sequencing, and seven of microsatellite markers were validated as informative genetic markers that can be utilized to study the T. indicum population.